E-148 Endovascular therapy in ischemic stroke with acute large vessel occlusion-recovery by endovascular salvage for cerebral ultra-acute embolism japan registry 2. (22nd July 2018) - Yoshimura, S; Sakai, N; Yamagami, H; Morimoto, T
Abstract : Background: Endovascular therapy has been shown to be effective in patients with acute cerebral large vessel occlusion, but real-world efficacies are unknown. Methods: We conducted prospective registry at 46 centers in Japan between October 2014 and January 2017. Eligible patients were patients with acute cerebral large vessel occlusion aged 20 years or older, hospitalized within 24 hours of the onset. We enrolled both consecutive patients who were treated with or without endovascular therapy. Endovascular therapy included thrombectomy, balloon angioplasty, stenting, local fibrinolysis, and piercing. The primary outcome was a favorable outcome as defined by a modified Rankin Scale (mRS) of 0–2 at 90 days after onset. Secondary outcomes were mRS of 0–1 and mortality. Safety outcomes were intracerebral hemorrhage or a recurrence of ischemic stroke. We constructed the matched cohort based on a propensity score for endovascular therapy and estimated the adjusted odds ratio [OR]. Results: A total of 2420 patients were recruited, 2399 (1, 278 in endovascular therapy vs 1121 in no endovascular therapy) provided the primary outcome at 90 days, and 2242 (1, 121 each) propensity score matched cohort was analyzed. Favorable outcomes were observed in 35.3% and 30.7% of patients in the endovascular therapy and no endovascular therapy groups, respectively (p = 0.02). The adjusted OR for the favorable outcome was 1.44 (95% confidence interval [CI]: 1.10–1.86, p=0.007). The efficacy of endovascular therapy in achieving favorable outcomes did not differ between our subgroups. Conclusions: Endovascular therapy decreased disabilities at 90 days in real-world patients with acute cerebral large vessel occlusion. Disclosures: S. Yoshimura: 1; C; Medtronic, Medicos Hirata, Termo, Bristal-Myers Squibb, Otsuka. 3; C; Boehringer-Ingelheim, Otsuka, Bayer, Sanofi, Phizer, Bristal-Myers Squibb, Stryker, Medtronic, Mitsubishi Tanabe. N. Sakai: 1; C; Termo. 2; C; Medtronic, Jimro. 3; C; Jimro, Otsuka, Johnson and Johnson, Medtronic, Stryker, Medico's Hirata. H. Yamagami: 1; C; Bristol-Myers Squibb. 2; C; Daiichi-Sankyo, Bayer, Boehringer Ingelheim. 3; C; Bayer, Daiichi-Sankyo, Bristol-Myers Squibb, Boehringer Ingelheim, Stryker. T. Morimoto: 2; C; Asahi Kasei, Boston Scientific, Bristal-Myers Squibb. 3; C; AbbVie, AstraZeneca, Daiichi Sankyo, Kyorin, Mitsubishi Tanabe, Phizer.